2008
DOI: 10.5195/jyd.2008.317
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teens for Success: Building 21st Century Skills through a 4-H Work-Based Learning Program

Abstract: There is widespread concern that youth lack the skills essential for job success and are entering the workplace unprepared. To address issues of workforce preparation, Extension educators at an urban 4-H education center created the Job Experience and Training (JET) program, a work-based learning program for teens. JET is conducted over a six-month period, culminating in an eight-week summer work experience in collaboration with a local park district. Supervisors and teens completed a performance appraisal mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Many youth in the United States enter the workforce temporarily, seasonally, or part-time prior to graduating from high school [IOM 1998;Morisi 2008]. Although recent studies have shown a decrease in the number of working youth [Smith 2011;Sum 2008], there are still millions who work to earn money, autonomy, socialization, and job skills [Ferrari 2003;Ferrari et al 2008;IOM 1998]. Skills learned on the job are valuable in daily life and help youth transition from being a student to being an employee [Ferrari 2003;Ferrari et al 2008].…”
Section: Moving Forward In Prevention Backgroundmentioning
confidence: 99%
“…Many youth in the United States enter the workforce temporarily, seasonally, or part-time prior to graduating from high school [IOM 1998;Morisi 2008]. Although recent studies have shown a decrease in the number of working youth [Smith 2011;Sum 2008], there are still millions who work to earn money, autonomy, socialization, and job skills [Ferrari 2003;Ferrari et al 2008;IOM 1998]. Skills learned on the job are valuable in daily life and help youth transition from being a student to being an employee [Ferrari 2003;Ferrari et al 2008].…”
Section: Moving Forward In Prevention Backgroundmentioning
confidence: 99%
“…Work-based learning enables youth to have real work experiences that are coupled with supports that help them to learn about themselves and to understand the expectations of the world of work (Cochran & Ferrari, 2009;Ferrari, Arnett, & Cochran, 2008). In this approach, youth are learning workplace skills through work in a concrete way rather than learning about work in an abstract sense or learning about a specific career path.…”
Section: Workforce Skills and Work-based Learningmentioning
confidence: 99%
“…There were two ratings given: a retrospective rating of skill level as perceived at the start of the process and another rating post-camp. We used this method because it reduces response-shift bias, that is, the tendency to rate oneself high at the beginning of an educational program (e.g., Marshall, Higginbotham, Harris, & Lee, 2007;Rockwell & Kohn, 1989), and also based on its success with other workforce preparation programs (Ferrari et al, 2008). The ratings were given on a five-point scale: (1) needs significant improvement, (2) needs some improvement, (3) demonstrates basic skill level, (4) sometimes excels, and (5) consistently excels.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Using multiple evaluation methods, several studies indicate that Adventure Central is meeting the developmental needs of its participants. Evaluation at Adventure Central has focused on aspects of overall program quality (Ferrari, Paisley, Turner, Arnett, Cochran, & McNeely, 2002) youth-adult relationships (Paisley & Ferrari, 2005), motivation for participation and retention of teens (Ferrari & Turner, 2006), parental perceptions (Ferrari, Futris, Smathers, Cochran, Arnett, & Digby, 2006), and workforce skills (Ferrari, Arnett, & Cochran, 2008).…”
Section: Program Settingmentioning
confidence: 99%